2012
DOI: 10.1016/j.pain.2012.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in spinal processing of transient and inflammatory colorectal stimuli in the rat

Abstract: Sex differences in the spinal processing of somatic and visceral stimuli contribute to greater female sensitivity in many pain disorders. The present study examined spinal mechanisms that contribute to sex differences in visceral sensitivity. The visceromotor response to colorectal distention (CRD) was more robust in normal female rats and following intracolonic mustard oil compared to males. No sex difference was observed in the CRD-evoked response of lumbosacral (LS) and thoracolumbar (TL) colonic afferents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 70 publications
4
43
0
Order By: Relevance
“…For example, sex differences in pain responsiveness and differences in regional brain activity resembling that observed in IBS have been seen in male and female animals. [89][90][91][92][93][94] In rodents experimental methodology that includes CRD to assess visceral sensitivity or a mechanical stimulus applied to the hindpaw or tail to assess somatic sensitivity, have uncovered sex differences in nociceptive behaviors following ELS, with responses in females being greater than males. 92,95 Studies performed in adult rodent models have demonstrated that estrogen and progesterone modulate pain reporting, and that variations in the response to colonic distension occurred during the estrus cycle.…”
Section: Sex Linked Differences In Visceral Sensitivitymentioning
confidence: 99%
“…For example, sex differences in pain responsiveness and differences in regional brain activity resembling that observed in IBS have been seen in male and female animals. [89][90][91][92][93][94] In rodents experimental methodology that includes CRD to assess visceral sensitivity or a mechanical stimulus applied to the hindpaw or tail to assess somatic sensitivity, have uncovered sex differences in nociceptive behaviors following ELS, with responses in females being greater than males. 92,95 Studies performed in adult rodent models have demonstrated that estrogen and progesterone modulate pain reporting, and that variations in the response to colonic distension occurred during the estrus cycle.…”
Section: Sex Linked Differences In Visceral Sensitivitymentioning
confidence: 99%
“…We and others have reported sex differences in the visceromotor response to colorectal distention (Figure 1) with the majority of studies indicating females have greater sensitivity (greater magnitude visceromotor response) than males in both rats and mice (Holdcroft et al, 2000; Ji et al, 2006; Ji et al, 2012b; Kamp et al, 2003). Similar results were reported using alternate responses (hindquarter elevation) to colorectal distention (Bourdu et al, 2005).…”
Section: Animal Studies Supporting a Sex Difference And Hormonal Mmentioning
confidence: 87%
“…Spinal administration of the NDMA receptor antagonist APV dose-dependently attenuated the visceromotor response to colorectal distention with greater effect in males. This corresponded with greater cell membrane expression of the GluN1 subunit of the NMDA receptor in the dorsal horn in females, suggesting females had more functional NMDA receptors (Ji et al, 2012b). This was likely due to E2 modulation of NMDA receptor activity.…”
Section: Animal Studies Supporting a Sex Difference And Hormonal Mmentioning
confidence: 93%
“…Thus different models may show different mechanisms underlying sexual dimorphism. Greater excitability of dorsal horn neurons in female rats may contribute to such sex differences (Ji et al 2012). Further, sexual dimorphism in the autonomic system may also contribute, as females differ substantially in their response to vagotomy and medullectomy in both bradykinin- and epinephrine-evoked muscle pain (Khasar et al 2003c).…”
Section: Sex Differences In Chronic Muscle Painmentioning
confidence: 99%